2014
DOI: 10.1016/j.jpeds.2014.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Variation in the Mu-Opioid Receptor Gene in Infants with Neonatal Abstinence Syndrome

Abstract: Objective Neonatal abstinence syndrome (NAS) from in utero opioid exposure is highly variable with genetic factors appearing to play an important role. Epigenetic changes in cytosine:guanine (CpG) dinucleotide methylation can occur after drug exposure and may help to explain NAS variability. We correlated DNA methylation levels in the mu-opioid receptor (OPRM1) promoter in opioid-exposed infants and correlate them with NAS outcomes. Study design DNA samples from cord blood or saliva were analyzed for 86 infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 31 publications
6
72
1
Order By: Relevance
“…Similarly, seven CpG sites showed significant hypermethylation of blood DNA taken from male opioid addicts when compared to blood DNA from controls (CpGs 5, 9, 10, 11, 18, and 23) 26. Increased methylation within the OPRM1 promoter (at −14, −10 [sites 10, 11]) was also found to be associated with worse neonatal abstinence syndrome outcomes in infants exposed to opioids in utero 42. It has been shown in mouse brain tissues that DNA methylation of the OPRM1 promoter decreases expression of the gene; through interaction with chromatin-remodeling factors, remodeling occurs, thus allowing access for Sp1 binding,43 which results in the MOR upregulation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, seven CpG sites showed significant hypermethylation of blood DNA taken from male opioid addicts when compared to blood DNA from controls (CpGs 5, 9, 10, 11, 18, and 23) 26. Increased methylation within the OPRM1 promoter (at −14, −10 [sites 10, 11]) was also found to be associated with worse neonatal abstinence syndrome outcomes in infants exposed to opioids in utero 42. It has been shown in mouse brain tissues that DNA methylation of the OPRM1 promoter decreases expression of the gene; through interaction with chromatin-remodeling factors, remodeling occurs, thus allowing access for Sp1 binding,43 which results in the MOR upregulation.…”
Section: Discussionmentioning
confidence: 89%
“…However, this approach has been employed successfully before 25,26,42. Fan and Zhang compared methylation profiles of human chromosome 6 ( OPRM1 gene location), derived from 12 tissues, and reported that CpG island methylation profiles were highly correlated between somatic tissues 57.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, variants in the OPRM1 and COMT genes were associated with shorter hospital stays and less need for treatment among infants with NAS (85). In addition, hypermethylation within the OPRM1 promoter was associated with worse NAS outcomes (86). …”
Section: Pregnant Women: Special Considerationsmentioning
confidence: 99%
“…A group of investigators showed similar higher levels of methylation on the OPMR1 promoter in the saliva and blood of infants with neonatal abstinence syndrome. However, the study could not determine whether the epigenetic change was a pre-existing risk factor or a change caused by the opioid exposure itself [21].…”
Section: Limitationsmentioning
confidence: 99%